Prevalence and risk factors of Brucella spp. in goats in Borana pastoral area, Southern Oromia, Ethiopia - Teshome, D.; Sori, T.; Banti, T.; Kidane, G.; Wieland, Barbara; Alemayehu, Gezahegn (Elsevier, 2022)
Goat production plays an important role in the livelihood of Borana pastoralists. Optimal utilization of the goat population, is however, impaired by diseases such as brucellosis. Brucellosis is considered as one of the serious diseases incurring considerable loss to the goat industry through reproductive wastages. The situation of brucellosis has not been investigated in goats in Borana pastoral areas despite the frequent occurrence of abortion. This study wasconducted from November 2016 to April 2017, aimed at determining the prevalence of infection with Brucella species, identify the risk factors of infection and understand the knowledge, attitude and practice (KAP) of pastoralists about the disease. Serum samples were collected from a total of 789 goats from three randomly selected pastoral districts. The samples were tested using a competitive enzyme-linked immunosorbent assay (cELISA). The study survey results showed that most of the pastoralists (≥64.2 %) and (≥81.6 %) had poor knowledge about brucellosis and its zoonotic importance, respectively. From a total of 789 sera samples 137 (17.36 %; 95 % CI: 14.78, 20.19) tested positive for anti-Brucella antibodies. The highest seroprevalence was observed in Elwaya (71/252; 28.17 %; 95 % CI: 22.71, 34.16) followed by Moyale (48/332; 14.46 %; 95 %CI: 10.86, 18.71), whereas the lowest prevalence was observed in Yabello district (15/208; 8.78 %; CI: 5.29, 13.52). The results of multivariable logistic regression analysis revealed that sex and age of goats were significantly associated with seroprevalence of brucellosis. The odds of infection was nearly 7 times (OR: 6.97) higher in female goats than in males (P < 0.001). Adult goats were 12 times (OR: 12.19) more likely to be infected than their younger counterparts (P < 0.001). For goats raised in large sized flocks (OR = 2.57; P = 0.028) and for those goats originated from Elwaya district, the risk of infection was significantly higher (OR = 7.91; P < 0.001). The history of occurrence of reproductive problems in female goats is significantly associated with seropositivity to Brucella infection (OR = 5.32; P < 0.001). This study showed that a significant proportion of goats in Borana pastoral districts were infected with Brucella, suggesting its economic implication and zoonotic importance.